ANTARA HIDUP DAN MATI: KAJIAN TEOLOGIS TERHADAP KONSEP MATI SURIH DAN ISU BUNUH DIRI - Oktavianus Aji Suleman; Febrianti Dita, Christiani Sambo Bungin, Selmi Utari Tandibilang, Fransisca Christine Lotong, Yoan P (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article examines theological research on the concepts of ‘natural death’ and suicide, and discusses religious perspectives on life and death. The Hadith Qudsi provides an in-depth understanding of the meaning of asphyxia and death from an Islamic perspective. In Islam, death means the separation of a person's body and soul, so that the human body no longer functions. It is important to note that religion, including Islam, prohibits suicide. It is emphasised that Allah forbids us to reject our own lives, as life and death are not under human control but under the control of God. The Western scientific approach also provides insights into near-death experiences (NDEs), which are often transcendental in nature. These experiences can provide additional perspectives on the issues of life, death, and existence. In a controversial context, euthanasia, which relates to the right to die, is also discussed. Although controversial, it is important to remember that suicide in a religious context remains condemned, as does the attempt to understand the meaning of life and death from a theological perspective. The aim of this study is to provide a deeper understanding of suicide. This understanding forms the basis for a more detailed explanation of the concept and an in-depth explanation of its philosophical and theological roots. It is important to consider society's views on suicide. Attention is also paid to the concepts of life and death in Islam, and it is evident that references to death and life in Islam represent an interconnected chain of life. This provides further context for understanding suicide from a religious perspective. In addition, this study refers to sociological perspectives such as the views of Emile Durkheim, who examined suicide sociologically using the approaches of selfish suicide, altruistic suicide, anomic suicide, and fatalistic suicide. This represents a multidisciplinary approach to understanding this complex phenomenon. This article provides answers to difficult questions about suicide. By elaborating on these concepts, this study provides a strong foundation for a deeper understanding of the complex phenomenon between life and death and helps answer critical questions about suicide proactively